Condylar volume and condylar area in class I, class II and class III young adult subjects - Saccucci, Matteo (BioMed Central, 2012)
AIM: Aim of this study was to compare the volume and the shape of mandibular condyles in a Caucasian young adult population, with different skeletal pattern. MATERIAL AND METHODS: 200 Caucasian patients (15–30 years old, 95 male and 105 females) were classified in three groups on the base of ANB angle: skeletal class I (65 patients), skeletal class II (70 patients) and skeletal class III (65 patients). Left and right TMJs of each subject were evaluated independently with CBCT (Iluma). TMJ evaluation included: condylar volume; condylar area; morphological index (MI). Condylar volumes were calculated by using the Mimics software. The condylar volume, the area and the morphological index (MI) were compared among the three groups, by using non-parametric tests. RESULTS: The Kruskal-Wallis test and the Mann Whitney test revealed that: no significant difference was observed in the whole sample between the right and the left condylar volume; subjects in skeletal class III showed a significantly higher condylar volume, respect to class I and class II subjects (p < 0.05); significantly lower condylar volume was observed in class II subjects, respect to class I and class III (p < 0.05). In the whole sample condylar volume (699.8 ± 63.07 mm(3) in males and 663.5 ± 81.3 mm(3) in females; p < 0.01) as well as condylar surface (423.24 ± 63.03 mm(2) in males and 389.76 ± 61.15 mm(2) in females; p < 0.01) were significantly higher in males than in females. CONCLUSION: Skeletal class appeared to be associated to the mandibular condylar volume and to the mandibular condylar area in the Caucasian orthodontic population.